2016
DOI: 10.1371/journal.pone.0161346
|View full text |Cite|
|
Sign up to set email alerts
|

Staphylococcus aureus and Lipopolysaccharide Modulate Gene Expressions of Drug Transporters in Mouse Mammary Epithelial Cells Correlation to Inflammatory Biomarkers

Abstract: Inflammation in the mammary gland (mastitis) is the most common disease in dairy herds worldwide, often caused by the pathogens Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). Little is known about the effects of mastitis on drug transporters and the impact on transporter-mediated excretion of drugs into milk. We used murine mammary epithelial HC11 cells, after lactogenic differentiation into a secreting phenotype, and studied gene expressions of ABC- and SLC- transporters after treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Pro-inflammatory cytokines, chemokines such as CXCL2, CCL20, and GRO1(CXCL1) have important roles in immune responses due to modulation of leukocyte infiltration (neutrophils and monocytes). CXCL2 has been determined as a biomarker of the inflammatory reaction previously [ 87 ]. It has been suggested that CXCL1 can be used as therapeutic targets, therapeutics, or biomarkers in mastitis [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, chemokines such as CXCL2, CCL20, and GRO1(CXCL1) have important roles in immune responses due to modulation of leukocyte infiltration (neutrophils and monocytes). CXCL2 has been determined as a biomarker of the inflammatory reaction previously [ 87 ]. It has been suggested that CXCL1 can be used as therapeutic targets, therapeutics, or biomarkers in mastitis [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of rheumatoid arthritis, there was an 85% increase in the duodenal permeability of a Chinese herbal medication, which was apparently due to a downregulation of membrane P-gp activity (Duan et al, 2017). In contrast, P-gp upregulation was observed during the assessment of an in vitro murine model of bovine mastitis caused by E. coli (reflected in the administration of LPS) or Staphylococcus aureus (Yagdiran et al, 2016). Murine mammary epithelial HC11 cells differentiated into a secreting phenotype exhibited a statistically significant increase in P-gp expression when incubated with LPS and S. aureus as compared with that associated with the control cell cultures.…”
Section: Studying Mechanisms Underlying Disease-induced Pk Changesmentioning
confidence: 98%
“…Murine mammary epithelial HC11 cells differentiated into a secreting phenotype exhibited a statistically significant increase in P-gp expression when incubated with LPS and S. aureus as compared with that associated with the control cell cultures. This outcome was interpreted as reflecting potential increases in drug and toxin secretion into the milk of lactating dairy cattle (Yagdiran et al, 2016).…”
Section: Studying Mechanisms Underlying Disease-induced Pk Changesmentioning
confidence: 99%
“…Moreover, Cp activates pathogen recognition in dairy cows that intramammary challenged with E. coli lipopolysaccharide [34]. Similarly, when treating mammary epithelial cells of murine with E. coli endotoxin or lipopolysaccharide S. aureus, up-regulation and transportation of some inflammatory marker genes are affected [35]. Both milk Cp and SAA levels depend on the method of measurement to be diagnostic tools for subclinical mastitis and many inflammatory diseases in dairy cattle [7,36].…”
Section: Escherichia Coli Staphylococcus Aureusmentioning
confidence: 99%